The witchwood crown - Williams, Tad (Williams, Tad. Last king of Osten Ard, 2017)
More than thirty years have passed since the events of the Memory, Sorrow, and Thorn trilogy, and the world has reached a critical turning point once again. The realm is threatened by divisive forces, even as old allies are lost, and others are lured down darker paths. Perhaps most terrifying of all, the Norns--the long-vanquished elvish foe--are stirring once again, preparing to reclaim the mortal-ruled lands that once were theirs....